Population Pharmacokinetics of Nifurtimox in Adult and Pediatric Patients With Chagas Disease. (10th May 2022) - Ince, Ibrahim; Prins, Klaas; Willmann, Stefan; Sutter, Gabriele; Hanze, Eva; Sadre‐Marandi, Farrah; Stass, Heino; Garmann, Dirk
Abstract: Nifurtimox (LAMPIT) has been used for decades for the treatment of Chagas disease, a chronic and potentially life‐threatening disease caused by the parasite Trypanosoma cruzi . The pharmacokinetic (PK) information on nifurtimox in humans derived from controlled clinical studies is very limited. The objective was to investigate and compare the population PK of nifurtimox in adult and pediatric patients with Chagas disease to confirm the clinical dosing regimen in children, which was based on allometric approaches using the concept that a dose‐equivalent exposure would reach equivalent antiparasitic efficacy as in adults. The resulting adult model adequately described the PK in adults. Significant predictors of the availability in PK were food intake, tablet formulation (fast‐ vs slow‐dissolution tablet), study, and body weight. As the resulting adult model could not adequately predict the sparse sampled pediatric patient data, these data were analyzed separately to derive exposure estimates for comparison with adult exposure. In the population PK model for pediatric patients, significant covariates were body weight and age. As compared to adults, children aged >2 years were estimated to have 50.6% higher apparent clearance. No hints of dose nonlinearity were observed in a dose range of 30 to 240 mg single dose in adults and 15 to 300 mg 3 times daily (8‐20 mg/kg) in children. Altogether, this study retroactively showed that the current mg/kg dosing regimen in children reached similar exposure as in adults receiving an 8 mg/kg total daily dose.